Cover Image. Issue 18 (5th November 2019) - Dzafic, Ilvana; Oestreich, Lena; Martin, Andrew K.; Mowry, Bryan; Burianová, Hana
Abstract : COVER ILLUSTRATION The Stria Terminalis . A white‐matter pathway that connects the amygdala to the bed nucleus of the stria terminalis, the hippocampus, caudate, thalamus, and which branches out to multiple septal and hypothalamic nuclei. The function of stria terminalis is crucial, as this white‐matter pathway is altered in anxiety, post‐traumatic stress disorder, and disorders of consciousness. In our study, for the first time, we elucidate a role for the stria terminalis in human social behaviour. Specifically, we found that increased microstructure of the right stria terminalis was related to faster detection of naturalistic emotion in threatening conditions.